2013
DOI: 10.3386/w19741
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Paid Family Leave in California on Labor Market Outcomes

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…This latter study analyzes individual micro data on women workers and concentrates solely on changes in maternity leave usage relative to other leaves . Baum and Ruhm (), using micro data from the 1997 National Longitudinal Survey, also echo this finding that the CPFL raised leave‐taking by about 3 weeks for the average mother.…”
Section: Introductionmentioning
confidence: 79%
“…This latter study analyzes individual micro data on women workers and concentrates solely on changes in maternity leave usage relative to other leaves . Baum and Ruhm (), using micro data from the 1997 National Longitudinal Survey, also echo this finding that the CPFL raised leave‐taking by about 3 weeks for the average mother.…”
Section: Introductionmentioning
confidence: 79%
“…For instance, a recent study on the effects of PFL in California found that maternity leave periods increased by a mean of 3 weeks post‐PFL implementation, and increases were most pronounced for less advantaged mothers, including those with lower levels of educational attainment, minority mothers, and single mothers (Rossin‐Slater et al, ). In a related study, PFL in California was also associated with an 18% increase in the likelihood of new mothers working in the year following a birth, with some indications of modest wage increases over the same period (Baum & Ruhm, ). Despite evidence that suggests California's PFL program may have produced positive effects on leave‐taking, job continuity, and wages, concerns remain that PFL programs may not go far enough to protect low‐income single‐mother families—who face heightened financial insecurity around the time of birth (Stanczyk, )—from postbirth economic deprivation.…”
Section: Background and Literature Reviewmentioning
confidence: 95%
“…PFL programs are associated with longer leave periods from work by new mothers, greater job continuity, and some evidence of wage improvements over time (Baum & Ruhm, ; Rossin‐Slater et al, ). For instance, a recent study on the effects of PFL in California found that maternity leave periods increased by a mean of 3 weeks post‐PFL implementation, and increases were most pronounced for less advantaged mothers, including those with lower levels of educational attainment, minority mothers, and single mothers (Rossin‐Slater et al, ).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…all leave types combined). Baum and Ruhm () study the impact of the same policy change using different data (the 1997 cohort of the National Longitudinal Survey of Youth) which provide more detail on the leave taking than the snapshot of leave taking observed through the March Current Population Survey data from 1999 to 2010 used by Rossin‐Slater et al . Baum and Ruhm's approach involves a multivariate difference in difference analysis using parents from control states without a paid family leave scheme.…”
Section: Introducing Paid Parental Leavementioning
confidence: 99%